Does ASEAN Freer Trade Benefit Malaysia? - Jamal Othman; Yaghoob Jafari (Aussenwirtschaft, 2010)
This paper examines the impact of intra-ASEAN trade liberalization (AFTA) using a multicountry, computable general equilibrium model (GTAP Model) with special focus onMalaysia. The study considers the full elimination of intra-ASEAN import taxes and export subsidies. Results suggest that Malaysia's GDP would only increase marginally while the effects on the individual commodity sectors in the country differ substantially. Specifically, Malaysian processed food and textiles are anticipated to expand pronouncedly following the intra-ASEAN freer trade.
Keywords: F15; D58; 330